Circulating extracellular vesicles promote recovery in a preclinical model of intracerebral hemorrhage - Fernando Laso-García; Laura Casado-Fernández; Dolores Piniella; Mari Carmen Gómez-de Frutos; Jone Karmele Arizaga-Echebarria; María Pérez-Mato; Elisa Alonso-López; Laura Otero-Ortega; Susana Belén Bravo; María del Pilar Chantada-Vázquez; José Avendaño-Ortiz; Eduardo López-Collazo; et al. (Elsevier, 2023)
Circulating extracellular vesicles (EVs) are proposed to participate in enhancing pathways of recovery after stroke through paracrine signaling. To verify this hypothesis in a proof-of-concept study, blood-derived allogenic EVs from rats and xenogenic EVs from humans who experienced spontaneous good recovery after an intracerebral hemorrhage (ICH) were administered intravenously to rats at 24 h after a subcortical ICH. At 28 days, both treatments improved the motor function assessment scales score, showed greater fiber preservation in the perilesional zone (diffusion tensor-fractional anisotropy MRI), increased immunofluorescence markers of myelin (MOG), and decreased astrocyte markers (GFAP) compared with controls. Comparison of the protein cargo of circulating EVs at 28 days from animals with good vs. poor recovery showed down-expression of immune system activation pathways (CO4, KLKB1, PROC, FA9, and C1QA) and of restorative processes such as axon guidance (RAC1), myelination (MBP), and synaptic vesicle trafficking (SYN1), which is in line with better tissue preservation. Up-expression of PCSK9 (neuron differentiation) in xenogenic EVs-treated animals suggests enhancement of repair pathways. In conclusion, the administration of blood-derived EVs improved recovery after ICH. These findings open a new and promising opportunity for further development of restorative therapies to improve the outcomes after an ICH.